Civil war: black panther ebook Black panther - special. - Hudlin, Reginald (Civil War: Black Panther., 2014)
Collects Black Panther (2005) #19-25. The Royal Couple, King T'Challa and Queen Ororo, embark on a diplomatic tour that will have them spanning the globe - and beyond! Stops include Latveria (Dr. Doom), the Moon (Black Bolt and the Inhumans), Atlantis (Namor the Sub-Mariner) and the Civil War-ravaged United States, for a meeting with none other than the point man for the U.S. government's implementation of the Superhuman Registration Act: Tony Stark, T'Challa's former Avengers teammate. Will the Black Panther and Storm decide to get off the sidelines of the Civil War and get involved?